Managing Visually Impaired Students: Factors that Support and Inhibit Inclusive Programs in Elementary - Hasan M. Al Shaban Radi; Zahyah Hanafi (Universitas Pendidikan Indonesia (UPI), 2024)
This study was designed to examine how elementary school principals managed visually impaired students in their schools. Thus, the objective of this study is to identify the factors that support or inhibit inclusion programs in three elementary schools in the district of Al-Ahsa in Saudi Arabia. These elementary schools were identified by key leaders in Al-Ahsa Educational Directory based on the principal’s favorable position toward inclusion. Data was collected through interviews with the three principals. Studies have indicated that the successful inclusion of students with visual impairment is largely due to the cooperation and commitment of principals. Findings found that the three principals were generally distinguishable from traditional educational administrators. Their roles were complex, and their schools were improving consistently even though problems surfaced that presently needed to be addressed. In the three schools, it was clear that leadership was shared and connected to the process of achieving inclusion. The findings in this study would be particularly useful to persons responsible for restructuring their school and implementing change to better meet the needs of all students.